Monocyte cell membrane-derived nanoghosts for targeted cancer therapy. Issue 13 (15th March 2016) - Krishnamurthy, S.; Gnanasammandhan, M. K.; Xie, C.; Huang, K.; Cui, M. Y.; Chan, J. M.
Abstract : Core–shell type 'nanoghosts' were synthesized with a biodegradable PLGA core and a monocyte cell membrane-derived shell. The ∼200 nm doxorubicin-loaded nanoghosts showed greater cellular uptake and cytotoxicity compared to non-coated nanoparticle controls in metastatic MCF-7 breast cancer cell lines. Abstract : Core–shell type 'nanoghosts' were synthesized with a drug-loaded biodegradable PLGA core and a monocyte cell membrane-derived shell. The nanoghosts were monodisperse with an average size <200 nm, and showed good serum stability for 120 h. Doxorubicin-loaded nanoghosts showed greater cellular uptake and cytotoxicity compared to non-coated nanoparticle controls in metastatic MCF-7 breast cancer cell lines.